Diagnostic Biomarkers in Women With Suspected Preeclampsia in a Prospective Multicenter Study. Issue 2 (August 2016) - Duckworth, Suzy; Griffin, Melanie; Seed, Paul T.; North, Robyn; Myers, Jenny; Mackillop, Lucy; Simpson, Nigel; Waugh, Jason; Anumba, Dilly; Kenny, Louise C.; Redman, Christopher W. G.; Shennan, Andrew H.; et al.
Abstract : OBJECTIVE: To evaluate 47 biomarkers (selected from the current medical literature), in isolation or in combination with placental growth factor (PlGF), to determine the need for delivery within 14 days, in women presenting with suspected preterm preeclampsia. METHODS: In a prospective, multicenter observational study, 47 biomarkers were measured in 423 women presenting with suspected preterm preeclampsia (in two prespecified groups: group 1 at less than 35 weeks of gestation and group 2 presenting between 35 0/7 and 36 6/7 weeks of gestation) to evaluate their ability to determine the primary endpoint: preeclampsia requiring delivery within 14 days. Using factor analysis and stepwise logistic regression, we sought one or more additional biomarkers for optimal determination of the primary endpoint. RESULTS: In women presenting at less than 35 weeks of gestation (n=286), the best performing combination of PlGF, podocalyxin, endoglin, procalcitonin (receiver operating curve [ROC] area 0.90, 95% confidence interval [CI] 0.86–0.93) was not statistically better than PlGF alone (ROC 0.87, 95% CI 0.83–0.92; P =.43) for preeclampsia requiring delivery within 14 days. Two other single markers had test performance that was not significantly different to PlGF (soluble fms-like tyrosine kinase-1 [sFlt-1] ROC 0.83, 95% CI 0.78–0.88; endoglin ROC 0.83, 95% CI 0.79–0.88). Similar findings were found in women presenting between 35 0/7 and 36 6/7 weeks of gestation (n=137): ROC for PlGF alone 0.75 (95% CI 0.67–0.83); ROC for PlGF, cystatin, pregnancy-associated plasma protein A in combination 0.81 (95% CI 0.74–0.88; P =.40). CONCLUSION: This study supports the growing body of evidence that a single angiogenesis-related biomarker (PlGF, sFlt-1, or endoglin) alone represents a useful diagnostic test for women presenting with suspected preterm preeclampsia. Abstract : Supplemental Digital Content is Available in the Text.In women with suspected preterm preeclampsia, a single angiogenesis-related biomarker is a useful diagnostic test to determine preeclampsia that requires delivery within 14 days.